Pengaruh penambahan ekstrak jahe merah (Zingiber officinale) pada susu terhadap uji fisikokimia dan organoleptik ginger milk curd - Intan Wulandari; Muh. Aniar Hari Swasono (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2022)
Ginger (Zingiber officinale) is a member of the Zingiberaceae family. The branched ginger rhizome is yellowish white and has fiber. Ginger rhizome is generally segmented and the skin is easy to peel and has a fragrant smell and spicy taste so that ginger can be used as an additive in food and beverages. Ginger milk curd is a dessert or preparation by mixing milk and ginger juice. Protease enzymes in ginger convert milk from liquid to semi-solid like pudding. This study aims to determine the effect of adding the ginger extract to milk on physical, chemical, and organoleptic tests of ginger milk curd and to obtain the best treatment from the addition of ginger extract concentration of ginger milk curd. The method used in ginger milk curd research is a completely randomized design (CRD) with 5 treatments and 5 replications so that 25 trials are obtained. The analysis carried out is physicochemical analysis including protein, pH, viscosity, and organoleptic including taste, color, and aroma. The best results were in treatment J4 (addition of 25% ginger extract concentration). With the results of the physicochemical test, protein content was 1.394%, pH 7%, viscosity was 3.278 (cP), the taste was 1.76 (slightly liked), color was 3.28 (liked) and the aroma was 3.64 (liked very much).